Comparison of COVID-19 disease between young and elderly patients: Hidden viral shedding of COVID-19. Issue 1 (January 2021) - Mori, Hitoshi; Obinata, Hirofumi; Murakami, Wakana; Tatsuya, Kodama; Sasaki, Hisashi; Miyake, Yu; Taniguchi, Yasuaki; Ota, Shinichiro; Yamaga, Mitsuki; Suyama, Yohsuke; Tamura, Kaku
Abstract: Objectives: The symptoms of Coronavirus disease 2019 (COVID-19) vary among patients. The aim of this study was to investigate the clinical manifestation and disease duration in young versus elderly patients. Methods: We retrospectively analyzed 187 patients (87 elderly and 100 young patients) with confirmed COVID-19. The clinical characteristics and chest computed tomography (CT) extent as defined by a score were compared between the two groups. Results: The numbers of asymptomatic cases and severe cases were significantly higher in the elderly group (elderly group vs. young group; asymptomatic cases, 31 [35.6%] vs. 10 [10%], p < 0.0001; severe cases, 25 [28.7%] vs. 8 [8.0%], p = 0.0002). The proportion of asymptomatic patients and severe patients increased across the 10-year age groups. There was no significant difference in the total CT score and number of abnormal cases. A significant positive correlation between the disease duration and patient age was observed in asymptomatic patients (ρ = 0.4570, 95% CI 0.1198–0.6491, p = 0.0034). Conclusions: Although the extent of lung involvement did not have a significant difference between the young and elderly patients, elderly patients were more likely to have severe clinical manifestations. Elderly patients were also more likely to be asymptomatic and a source of COVID-19 viral shedding.